2009
DOI: 10.1093/humrep/den502
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic screening outcomes are associated with culture conditions

Abstract: These results suggest that a laboratory procedure change may significantly impact PGS patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Beyer and colleagues showed an improvement in livebirth rates in women R40 years with less than two previous stimulated IVF cycles after changing embryo culture media after biopsy (168). Media become especially important in terms of pH buffering during the biopsy procedure.…”
Section: Embryo Biopsy Technique Is Important For Maintaining Embryo Qualitymentioning
confidence: 99%
“…Beyer and colleagues showed an improvement in livebirth rates in women R40 years with less than two previous stimulated IVF cycles after changing embryo culture media after biopsy (168). Media become especially important in terms of pH buffering during the biopsy procedure.…”
Section: Embryo Biopsy Technique Is Important For Maintaining Embryo Qualitymentioning
confidence: 99%
“…Studies ( 7 ) exploring the relationship between body mass index (BMI) and euploidy have yielded inconclusive results, and some degree of controversy remains. In addition, laboratory procedures, including culture conditions and blastocyst morphology, can affect the rate of aneuploidy ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, early reports described that LH-containing gonadotropins may improve embryonic euploidy compared with pure FSH stimulation, but this has not been further corroborated (8,9). Moreover, it has been reported that laboratory conditions can affect pregnancy rates (10,11). It is worth noting many of these studies were performed using older PGT-A techniques, mainly with fluorescent in situ hybridization, but there is a lack of data using more sensitive modalities, including nextgeneration sequencing (NGS) (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%